SISTEM INFORMASI PENJUALAN TIKET PERTANDINGAN SEPAKBOLA DI STADION JATIDIRI SEMARANG (Information Technology and Telematics, 2013)
In the modern life, the grow of information technology has been good. Most of all of part of live. All of them use the computer system. It is not only use to help the human problems but for subtituting the peoples work that doesn’t need daily think and activity an example in information system is the marketing information system. Such as the ticket marketing on football match. The researcher create an information ticket marketing on football match with the aim and purpose to give a better service for the newers and give the simple ticket distribution and making a ticket report selling. This system build on Delphi 7 and MySQL. The product of this system the viewers can buy the ticket at the locket easyly and comfortable. Viewers can know the quota from the information system on the monitor and the official can be easy controling the ticket selling and reduce the ilegal viewers. Keywords : Information System, Football Match Ticket Marketing